PENGARUH AUDIT TENURE, AUDIT DELAY, DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris Pada Perusahaan Sektor Retailing di Bursa Efek Indonesia Tahun 2019 - 2023) - Beta Zuhruful Baity; Fina Fitriyana (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to empirically test and prove the Effect of Audit Tenure, Audit Delay, and Audit Committee on Audit Quality. The population of this study is companies listed on the Indonesia Stock Exchange for the period 2019 to 2023, totaling 30 companies. Sampling using purposive sampling technique so that a sample of 20 companies was obtained with observations for 5 (five) years so that a total of 100 financial reports and audited annual reports were obtained. The data analysis method uses logistic regression analysis and hypothesis testing with a significance level of 5%. The test tool used is the E-Views 13 program. Based on the results of the hypothesis test, it shows that Audit Tenure, Audit Delay, and Audit Committee simultaneously have a significant effect on Audit Quality. Partially, only the Audit Committee has a significant effect on Audit Quality, while Audit Tenure, Audit Delay do not have a significant effect on company value.